2004
DOI: 10.1002/path.1567
|View full text |Cite
|
Sign up to set email alerts
|

Hyperphosphorylation of pRb: a mechanism for RB tumour suppressor pathway inactivation in bladder cancer

Abstract: Loss of heterozygosity, mutations or deletions of the RB1 gene usually result in loss of pRb expression, which has been regarded as an indicator of loss of pRb function in human tumours. It has previously been shown that in addition to loss of pRb expression, aberrantly high (pRb2+) pRb expression also indicates loss of pRb function in bladder tumours compared with moderate (normal, pRb1+) pRb expression. The aim of this study was to elucidate the mechanism by which pRb is functionally inactivated in bladder t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 12 publications
2
50
1
5
Order By: Relevance
“…INK4a expression, but this association is not systematic (Sartor et al, 1999;Chatterjee et al, 2004). In our series, various levels of phosphorylation of pRb were observed despite the lack of expression of INK4a.…”
Section: Tp53 and Rb1 Pathways In Radiation-induced Sarcomas N Gonin-contrasting
confidence: 47%
See 1 more Smart Citation
“…INK4a expression, but this association is not systematic (Sartor et al, 1999;Chatterjee et al, 2004). In our series, various levels of phosphorylation of pRb were observed despite the lack of expression of INK4a.…”
Section: Tp53 and Rb1 Pathways In Radiation-induced Sarcomas N Gonin-contrasting
confidence: 47%
“…Electrophoresis was run with 100 mg of protein extract on a NuPAGE 3-8% Tris-acetate gel (Invitrogen, Cergy Pontoise, France), and Western blotting was performed using a mouse anti-pRb antibody (14001A, BD Pharmigen, Erembodegem, Belgium, 1/250, overnight at 41C) after transfer on polyvinylidene difluoride membrane (Immobilon-P, Millipore Corp., Saint Guentin en Yveline, France). The antibody detected underphosphorylated (110 kDa) and hyperphosphorylated (116 kDa) pRb (Chatterjee et al, 2004 (Sharpless, 2005). In this series of sarcomas, we can conclude that, in addition to the cases with direct gene inactivation, the loss of Rb function occurred by hyperphosphorylation of the protein in three of 11 other tested tumours.…”
Section: Tp53 and Rb1 Pathways In Radiation-induced Sarcomas N Gonin-mentioning
confidence: 56%
“…Other studies have reported p16 promoter hypermethylation in ESFT to be rare; 1/24 (4%; Tsuchiya et al, 2000) and 2/19 (10%; Lopez-Guerrero et al, 2001). Heterogeneity of expression might therefore be effected through expression of wild-type p53, which can downregulate transcription from the p14 ARF and p16 promoter (Robertson and Jones, 1998), pRb hyperphosphorylation (Chatterjee et al, 2004) or overexpression of the bmi-1 gene (Jacobs et al, 1999). Homozygous and single copy deletions of the MTAP gene were observed in ESFT cell lines and primary tumour; homozygous deletions (but not single copy deletions) have previously been described with similar frequency to this study (Huang et al, 2005).…”
Section: Discussionmentioning
confidence: 97%
“…Phosphorylation of pRB1 is thus the key regulatory step in this pathway controlling cell division. Amplification of the cyclin D1 gene or mutations in p16 are often found in tumors contributing to a hyperphosphorylated state of pRB1 and a consequential commitment to continued cell growth (16,17).…”
Section: Ptm Of Nuclear Proteinsmentioning
confidence: 99%